2014
DOI: 10.1246/cl.140786
|View full text |Cite
|
Sign up to set email alerts
|

One-pot In Situ Synthesis of Hollow Layered Double Hydroxide–Ammonium Polyphosphate Nanoshells toward Flame Retardant

Abstract: A novel approach to synthesize nanostructure composites of layered double hydroxide–ammonium polyphosphate (LDH–APP) is reported. hollow LDH–APP nanoshells were synthesized by simply mixing precursor solutions and systematically characterized by scanning electron microscopy (SEM), transmission electron microscopy (TEM), X-ray diffraction (XRD), Fourier transform infrared (FTIR), and Brunauer–Emmett–Teller (BET) techniques. The as-fabricated LDH–APP–PP (polypropylene) composites using hollow LDH–APP nanoshells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Nevertheless, Bragg reflections with low intensity were observed in Mg 3 Al-APP LDH. This is perhaps because the APP-LDH become more amorphous, and thus there is insufficient coherence along the platelet stacking axis ( c -axis) to observe any high intensity (00 l ) Bragg reflection [29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, Bragg reflections with low intensity were observed in Mg 3 Al-APP LDH. This is perhaps because the APP-LDH become more amorphous, and thus there is insufficient coherence along the platelet stacking axis ( c -axis) to observe any high intensity (00 l ) Bragg reflection [29].…”
Section: Resultsmentioning
confidence: 99%
“…The band at 1365 cm −1 is attributed to the interlayer of CO3 2− . Besides, the bands at 1141, 907, and 1440 cm −1 are attributed to the vibrations of P–O and N–H group, respectively, demonstrating the presence of phosphate in the obtained APP-LDH nanoparticles [29]. The spectra results suggest a successful intercalation of APP molecules into the interlayers of LDH and that they were not decomposed.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, MgAlY-APP-LDHs contained a small number of low-intensity Bragg peaks. This may be because LDHs have become more amorphous, so the coherence along the platelet accumulation axis (c-axis) to notice any highintensity (001) Bragg reflection [45]. By comparing the XRD patterns of APP and LDHs, it can be found that no characteristic peaks of APP were observed in LDHs, which also confirms that APP molecules were successfully inserted into the interlayer of LDHs.…”
Section: Resultsmentioning
confidence: 96%